135k views
2 votes
Which expressions are equivalent to (k^(1/8))^(−1) ?

choose all answers that apply:
a. (k^(-1))^(1/8)

b. (8_/`k)^(-1)

c. k^(-1/8)

d. none of the above


* _/` is a radical with 8 as the index and k as the radicand

User Grendian
by
5.2k points

1 Answer

3 votes

The first option is correct: we have


\left(k^{(1)/(8)}\right)^(-1) = \frac{1}{k^{(1)/(8)}} = \frac{1}{\sqrt[8]{k}},\quad \left(k^(-1)\right)^{(1)/(8)} = \left((1)/(k)\right)^{(1)/(8)} = \frac{1}{\sqrt[8]{k}}

The second option is also correct, because it simply applies the definition


k^{(1)/(n)} = \sqrt[n]{k}

The third option is also correct, because it applies the rule


(a^b)^c = a^(bc)

User Anatoliy Kmetyuk
by
5.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.